Association Between Giving Birth During the Early Coronavirus Disease 2019 (COVID-19) Pandemic and Serious Maternal Morbidity. Issue 1 (27th January 2023) - Metz, Torri D.; Clifton, Rebecca G.; Hughes, Brenna L.; Sandoval, Grecio J.; Grobman, William A.; Saade, George R.; Manuck, Tracy A.; Longo, Monica; Sowles, Amber; Clark, Kelly; Simhan, Hyagriv N.; Rouse, Dwight J.; et al.
Abstract : Despite health care and societal modifications, giving birth during the early coronavirus disease 2019 (COVID-19) pandemic was not associated with increased risk of serious maternal morbidity from common obstetric complications. Abstract : OBJECTIVE: To evaluate whether delivering during the early the coronavirus disease 2019 (COVID-19) pandemic was associated with increased risk of maternal death or serious morbidity from common obstetric complications compared with a historical control period. METHODS: This was a multicenter retrospective cohort study with manual medical-record abstraction performed by centrally trained and certified research personnel at 17 U.S. hospitals. Individuals who gave birth on randomly selected dates in 2019 (before the pandemic) and 2020 (during the pandemic) were compared. Hospital, health care system, and community risk-mitigation strategies for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in response to the early COVID-19 pandemic are described. The primary outcome was a composite of maternal death or serious morbidity from common obstetric complications, including hypertensive disorders of pregnancy (eclampsia, end organ dysfunction, or need for acute antihypertensive therapy), postpartum hemorrhage (operative intervention or receipt of 4 or more units blood products), and infections other than SARS-CoV-2 (sepsis, pelvic abscess, prolonged intravenous antibiotics, bacteremia, deep surgical site infection). The major secondary outcome was cesarean birth. RESULTS: Overall, 12, 133 patients giving birth during and 9, 709 before the pandemic were included. Hospital, health care system, and community SARS-CoV-2 mitigation strategies were employed at all sites for a portion of 2020, with a peak in modifications from March to June 2020. Of patients delivering during the pandemic, 3% had a positive SARS-CoV-2 test result during pregnancy through 42 days postpartum. Giving birth during the pandemic was not associated with a change in the frequency of the primary composite outcome (9.3% vs 8.9%, adjusted relative risk [aRR] 1.02, 95% CI 0.93–1.11) or cesarean birth (32.4% vs 31.3%, aRR 1.02, 95% CI 0.97–1.07). No maternal deaths were observed. CONCLUSION: Despite substantial hospital, health care, and community modifications, giving birth during the early COVID-19 pandemic was not associated with higher rates of serious maternal morbidity from common obstetric complications. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT04519502.